Estratigrafía y análisis tafonómico de Bonitasaura salgadoi Apesteguía, en el sitio «La Bonita» (Cretácico superior, Rio Negro, Argentina) - Pérez, Leandro Martín (2009)
«La Bonita» is a fossiliferous locality close to the town of Cerro Policía, Río Negro Province, Argentina. At the quarry are exposed siliceous rocks belonging to the Bajo de la Carpa and Anacleto formations (Santonian-Campanian), separated by an unconformity from the Rentería Formation (Upper Pliocene-Pleistocene). The Bajo de la Carpa Formation is composed of sandstones, fine beds of conglomerates, alternate with pelites and wackes beds. The Anacleto Formation is composed of sandy to pelitic beds. The Rentería Formation is dominated by conglomerates with clasts that reach 15 cm in length, included in a sabullitic matrix. The facies analysis suggests a fluvial regime, with a subacuatic control with changes from mid to low energy. The lenticular-shaped sandy channels with crossed stratification point to an unidirectional flow in the transporting agent and bioclasts. The taphonomical analysis suggested that the dinosaur dies close to the river margins, being rapidly incorporated to the fluvial sediments that sepulted the specimen in successive events. The spatial distribution and bone relations suggest a very short transport from the source area, with a slight northward movement. The presence of two caudal vertebrae series with an opisthotonous articulation pattern, suggests that the animal was exposed long enough to permitt the rigor mortis and dissecation. The disarticulation degree also point to some amount of weathering of the skeleton before being sepulted. However, the exceptional periostium preservation in many cases suggests a very short subaerial exposure.